Stability Analysis and Numerical Simulation of the COVID-19 SISiR Model : Bahasa Indonesia - Arival Rince Putri; Berliani Nasran; Budi Rudianto (Jurnal Matematika, Statistika dan Komputasi, 2023)
This research discusses the SISiR model (Susceptible Infected Sick Recovered) considering individual immune parameters and lockdown parameters. The consideration of these parameters aims to determine whether immunity and lockdown have an impact on the spread of COVID-19. The model's stability is analyzed around the equilibrium point to understand the dynamics of COVID-19 spread in a population. Furthermore, the parameter R0 is determined to indicate whether COVID-19 disappears or remains in the population. From numerical simulations with spesific parameter values, it is concluded that COVID-19 continues to spread in the population with an R0 = of 4.4486. The addition and reduction of immune and lockdown parameters affect the spread of COVID-19.